Grammar and literacy in the Portuguese as an Additional Language teaching and learning - da Silva, Meire Celedônio (BELT - Brazilian English Language Teaching Journal, 2019)
The teaching of Portuguese as an Additional Language (PLA) has gained prominence in the internationalization activities of Brazilian universities, especially public ones. This study specifically addresses the context of the Federal University of Ceará (UFC). In the course offered by the Vernacular Letters Department, the students read and produce texts which are primarily academic textual genres. Thus, the goal of this study is to consider the role of teaching and learning grammar in the expansion of the literacy of PLA students. The theoretical approach used here is the Socio-discursive Interactionism and the language didactics theory. We also consider the theoretical discussions of Bulea (2015) on grammar education. Based on these considerations, it is shown that teaching PLA from an interactionist perspective while taking the teaching of grammar into account contributes significantly to increasing academic literacy.